Efisiensi Penggunaan Nitrogen (Nue) Dan Resorpsi Nitrogen Pada Hutan Taman Nasional Bukit Duabelas Dan Perkebunan Kelapa Sawit Di Kabupaten Sarolangun, Provinsi Jambi - Violita Violita (Bioscience, 2017)
Nitrogen use efficiency (NUE) plays an important role on plant adaptation to the low nutrient conditions. Transformation system from natural forest to oil palm plantation changedthe NUE and soil nutrition in ecosystem. However, how the transformation system affects NUE, N resorption, and soil nutrition in Sarolangun, Jambi province still unknown. The aims of the study were (1) to quantify NUE and Nresorptionand its correlation to N soil content (2)to determine nitrogen loss of litterfall in natural forest (HA) and oil palm plantation (KS) in Sarolangun, Jambi. The result showed that NUE in plant scale (NUE c) influenced by N resorption. NUE c increased with increasing of N resorption. Nitrogen and carbon content of the soil in HA was higher than that of in KS. There was no correlation between N soil content with foliar N content, N resorption, and NUE c. NUE in ecosystem scale (NUEES) was higher in HA than that of in KS. There was 68.3% of total N productionloss or out from the system inKS. Key words: NUE, N soil content, N resorption, transformation system